An Evaluation of Optical Constants of Organic Compounds in the solid State - Singh, G.; Singh, M.P.; Mishra, L.K. (Asian Journal of Chemistry, 2010)
Using Kramers-Kroing relation optical constants n, K, R and μ (real and imaginary part of refractive index, reflection and absorption coefficients) for organic materials have been evaluated. Our calculated results indicate that real part of the refractive index n is always less than 1 for these materials.